The role of psychosocial factors in the interprofessional management of women with chronic pelvic pain: A systematic review - Susanne G. R. Klotz; Clarissa Kolbe; Miriam Rueß; Christian A. Brünahl (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Chronic pelvic pain (CPP) is a common pain disorder in women associated with negative biopsychosocial consequences. The multifactorial etiology and maintaining aspects of CPP logically require an interprofessional treatment approach. However, the effects of interprofessional treatment strategies on psychosocial factors remain unclear. The study aims to investigate how interprofessional therapy helps to treat psychosocial factors in women with CPP. The systematic review summarizes the current evidence of interprofessional treatment in women with CPP. Material and methods A systematic literature review was performed in six databases (Medline, Web of Science, Cochrane Library, PEDro, CINAHL, and PsycINFO) until February 2023. Studies were selected in a two‐step approach applying as inclusion criteria the search combinations of Chronic Pelvic Pain and CPP, synonyms for interprofessional therapies, and for female patients. Studies were excluded if they were not quantitative primary research published in English, if CPP was not defined appropriately, if the study population was not female adult patients, if the interprofessional intervention was not operationalized appropriately, if they were single case studies, and if outcomes did not include at least one of the psychosocial factors pain, depressive symptoms, pain catastrophizing, fear, or anxiety. Risk of bias of the included studies was rated with the McMaster Critical Review Form. Studies were summarized narratively. The review is registered in PROSPERO (CRD42023391008). Results Five studies with a total sample size of n = 186 women were included, three of them were uncontrolled retrospective before‐after chart review. Only one study used a randomized controlled design, the other study used a non‐randomized controlled group. The studies' methodological quality is adequate with perspective of study design. The multiprofessional treatment approaches used in the studies differed with regard to professions involved, therapy methods, and modalities. Psychosocial outcome measures were pain (five studies), depressive symptoms (three studies), and anxiety symptoms (four studies). Conclusions Although interprofessional treatment strategies for women with CPP are recommended in existing guidelines, available evidence is scarce and does not allow for identification of the best interprofessional treatment approach. The effect on psychosocial factors remains unclear. More research is needed determining the best practice interprofessional treatment option for women with CPP.